EMPLOYEES TRAINING: AN INGREDIENT OF ORGANIZATIONAL SURVIVAL IN NIGERIA (A STUDY OF SELECTED SMALL AND MEDIUM SCALE ENTERPRISES IN PORTHARCOURT) - DIALOKE, ASS. PROF. IKECHUKWU,; EBIKESEYE, BIPELEDEI, (IJRDO - Journal of Applied Management Science, 2017)
This study examined Employees Training: An Ingredient of Organizational Survivalin Nigeria with Selected Small And Medium Scale Enterprises in Portharcourt as its case study.the study was guided by three research questions and hypotheses which are consistent with itsobjectives. The study employed the descriptive survey approach in its design and data wasgenerated from a five point likert scale questionnaire. The study covered a population of onehundred and forty three (143) employees of eight (8) SMEs within Portharcourt city. Theresearcher used purposive sampling technique to select 129 respondents as the sample; however,out of the 129 questionnaires distributed, only 112 were correctly filled and returned; therebygiven a questionnaire return rate of 87%. The statistical tools used for data analysis is theMannwhitney U test using the 20.0 version of statistical package for social sciences (SPSS). Itwas conclude that bearing the strategic contributions of employee training, training of employeesshould not just be seen as a fringe benefit for the individual staff by the organization or aninterventionist approach to temporarily solve organizational problems. Rather, they should beseen as an integral part of business functions that build a long-term strategic value for theorganization by helping the manpower acquire relevant skills, knowledge and experience thatcan help the organizations attain their long term goals. The study recommended that the cost ofemployee training in the SMEs should be controlled, in order to ensure that it does not negate thecompetitiveness of the organization. These SMEs in related businesses can achieve by jointlybuilding training schools in order to attain and maximize economies of scale, there is need toensure that training programmes are tailored along the skill gaps of the employees. This willensure that the employees contribute maximally to the sustainability of SMEs and that to ensurethat employee training contributes maximally to SMEs adaptability, the updating of workers’skill must be anchored on needs assessment, this will enhance the inclusion of current andrelevant skills in the training scheme of SMEs